The molecular insights of cyanobacterial bioremediations of heavy metals: the current and the future challenges - Lourembam, Jinita; Haobam, Banaraj; Singh, Kshetrimayum Birla; Verma, Savita; Rajan, Jay Prakash (Frontiers in Microbiology, 2024)
In recent years, over explorations of ore and growth of industries are prime factor to release of heavy metals in environments. As a result, the food crops and water bodies are contaminated with metals which may have several adverse effects on the health of humans and other living species. These metals and metalloids, like Zn, Cu, Mn, Ni, Cr, Pb, Cd, and As, upset the biochemical pathways of metabolite synthesis in living organisms and contribute to the etiology of different diseases. Microorganisms includes bacteria, archaea, viruses, and many unicellular eukaryotes which can span three domains of life and some microorganisms, such as cyanobacteria, have shown high efficiency in the biosorption rate of heavy metals. Cyanobacteria are suitable for bioremediation as they can grow in adverse environments, have a less negative impact on the surrounding environment, and are relatively cheaper to manage. The structure of cyanobacteria has shown no extensive internal-bound membranes, so it can directly employ the physiological mechanisms to uptake heavy metals from contamination sites. Such biochemical makeups are suitable for managing and bioremediating heavy metal concentrations in polluted environments. This review aims to explore the potential of cyanobacteria in the bioremediation of heavy metals and metalloids in water bodies. Additionally, we have identified the prospects for enhancing bioremediation effectiveness.